Who Benefits from Global Value Chain Participation? Does Functional Specialization Matter? - Petr Pleticha (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Global value chain (GVC) participation has transformed many lines of business. The benefits it provides in terms of greater specialization and technology diffusion, however, do not spread identically across countries and industries. This paper shows that taking into account the functional specialization helps to explain how the benefits of GVC participation are distributed. Using data for 35 industries in 40 countries in 2000-2011, we estimate the impact of GVC participation on value added within a production function framework. The results indicate that there is heterogeneity in the effects of GVC participation, according to the functional specialization of the respective industry and its GVC partners. Participating in R&D-related GVCs is especially profitable for fabrication-oriented industries and low-developed countries. It follows that any GVC participation analysis will be incomplete if it fails to take the functional specialization of the GVC participants into consideration.
Keywords: F02; F14; O33; O47; 330; global value chains; input-output analysis; technology diffusion; development